Oil Revenue and Sustainable Economic Growth in Nigeria: Empirical Analysis - Dauda, Musa; Alege, Philip O.; Ewetan, Olabanji O.; Asemota, Franklin F. (International Journal of Energy Economics and Policy, 2023)
In this study, the nexus between the generated oil revenue in Nigeria from 1981 to 2021 and its possible influences on the relative growth of the economy on a sustainable basis has been investigated. Utilizing the Johansen Co-Integration test, Granger Causality Technique as well as the Error Corrections Mechanism (ECM) to analyze the sourced data from both the World Development Indicators and the Nigeria Centra Bank. The findings depict the occurrence of a long-run connection amongst the variables of the study as both the eigenvalue test and trace test depict two and three cointegrating equations respectively at a 5% level of significance. 34.8% of short-run errors are rectified annually, according to the error correction mechanism. As a result, the coefficient reflects the rate of adjustment at which the RGDP’s short and long runs are tied together. Further findings reveal that economic growth (RGDP) granger caused oil revenue (OREV) and that the generated oil revenue in Nigeria (OREV) granger caused economic growth (RGDP) during the study period. This suggests that the generated oil revenue in Nigeria (OREV) and economic growth (RGDP) relationship is causally bidirectional. This study, therefore, recommends the creation and efficient implementation of policies that facilitate prudent identification, collection and utilization of the generated oil income and adequate deployment to critical underdeveloped and developing sectors of the economy.